Genetic Variation of Siam Orange (Citrus nobilis Lour.) in Several Sumatran Production Centers using RAPD Marker: Genetic Variation of Citrus nobilis Lour in Several Sumatran Production Centers - Arifa Setriani; Mansyurdin; Nurainas (Journal of Tropical Life Science, 2025)
Siam orange (Citrus nobilis Lour.) is a key horticultural commodity in Indonesia, valued for its adaptability, potential to improve farmer welfare, and contribution to the national economy. In Sumatra, four main production centres are located in Berastagi (North Sumatra), Gunung Omeh and Pasaman (West Sumatra), and Bangkinang (Riau). However, the origin of seedlings from these centres remains unclear. Despite high productivity, inconsistencies in fruit quality and genetic diversity among production centres highlight the need for molecular-level analysis to ensure superior varieties and maintain market competitiveness. This study aimed to determine the intra- and interpopulation genetic variations of Siam orange in these four production centres using RAPD markers. DNA isolation followed the Doyle and Doyle (1987) method, and amplification used 12 primers, of which OPA03, OPA10, and OPA01 produced the highest polymorphism (95.25%). Intrapopulation genetic variation was relatively low (H = 0.1061–0.1919), with Berastagi showing the lowest (H = 0.1061) and Gunung Omeh the highest (H = 0.1919). Interpopulation genetic diversity was classified as high (DST = 0.0619), with GST = 0.2946, and gene flow was Nm = 1.1975. UPGMA cluster analysis revealed that Gunung Omeh and Berastagi had the most significant genetic distance (0.1622), while Gunung Omeh and Bangkinang were the closest (0.0614). Principal Coordinates Analysis (PCoA) indicated that Berastagi individuals were more clustered, whereas Gunung Omeh, Pasaman, and Bangkinang were more dispersed. These findings indicate that while genetic variation within populations is limited, genetic differentiation among populations is substantial, offering opportunities to select and combine diverse genetic sources. This diversity can be strategically exploited in breeding programs to develop superior cultivars, improve fruit quality uniformity, and strengthen the commercial competitiveness of Siam orange cultivation in Sumatra.